2020
DOI: 10.1530/erc-19-0441
|View full text |Cite
|
Sign up to set email alerts
|

HEREDITARY ENDOCRINE TUMOURS: CURRENT STATE-OF-THE-ART AND RESEARCH OPPORTUNITIES: MEN1-related pancreatic NETs: identification of unmet clinical needs and future directives

Abstract: The PanNET Working Group of the 16th International Multiple Endocrine Neoplasia Workshop (MEN2019) convened in Houston, TX, USA, 27–29 March 2019 to discuss key unmet clinical needs related to PanNET in the context of MEN1, with a special focus on non-functioning (nf)-PanNETs. The participants represented a broad range of medical scientists as well as representatives from patient organizations, pharmaceutical industry and research societies. In a case-based approach, participants addressed early detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…This inhibitory effect, potentially useful in improving the quality of life in patients affected by recurrent PC, may occur both through a direct action on osteoclasts and osteoblasts and an indirect action via several cellular pathways ( 26 ). For these reasons, TKIs, such as cabozantinib ( 27 ), sorafenib ( 28 ), and vandetanib ( 29 ), were given in a few case studies reported in the last few years, and in some selected cases the drug choice was also guided by patient-specific mutation analysis ( 29 ). In one patient with PC in HPT-JT syndrome with lung metastatic disease, the use of sorafenib brought normocalcemia and radiographic stability of neck and lung tumors.…”
Section: Discussionmentioning
confidence: 99%
“…This inhibitory effect, potentially useful in improving the quality of life in patients affected by recurrent PC, may occur both through a direct action on osteoclasts and osteoblasts and an indirect action via several cellular pathways ( 26 ). For these reasons, TKIs, such as cabozantinib ( 27 ), sorafenib ( 28 ), and vandetanib ( 29 ), were given in a few case studies reported in the last few years, and in some selected cases the drug choice was also guided by patient-specific mutation analysis ( 29 ). In one patient with PC in HPT-JT syndrome with lung metastatic disease, the use of sorafenib brought normocalcemia and radiographic stability of neck and lung tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The existing therapeutic options for the various NENs have not been formally evaluated in MEN1 patients, being extrapolated from non-MEN1 NENs patients (Pieterman et al 2020). There is scarcity of evidence reporting on these anti-tumour therapies specifically in MEN1-NENs patients.…”
Section: Men1-nens: Limitations Of Current Therapiesmentioning
confidence: 99%
“…Screening should be performed every 1 to 3 years in patients without dpNETs and more frequently in patients with symptoms related to hormonal secretion or evident tumors ( 1 , 2 ). This approach, besides the inconvenience and requirement for continuous patient adherence, entails exposure to the risks of gadolinium deposits in several tissues and EUS-related complications ( 3 ). Currently existing serum biomarkers do not have the necessary negative predictive value to replace imaging as a mean of detecting patients at risk for progression or metastatic disease, making imperative the search for new biomarker classes ( 2 , 3 ).…”
mentioning
confidence: 99%
“…The findings of the present study are of particular interest as they may help identify MEN1 patients with dpNET who are at a higher risk for a more aggressive course irrespective of tumor size. Currently, the most widely used parameters to identify such patients are tumor size (≥ 2 cm), functionality, growth rate, and grade, but not all high-risk patients will develop metastases, and metastases may also occur in low-risk patients with lesions smaller than 2 cm ( 3 , 8 ). Additional biomarkers for predicting disease progression are currently missing, whereas evolving biomarkers such as the NETest have not been studied extensively in this patient group ( 3 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation